2020
DOI: 10.1158/1535-7163.mct-19-1116
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Blocking Therapy Decreases Survival of Tumor-Infiltrating Immunosuppressive Myeloid Cells and Enhances the Antitumor Efficacy of PD-1 Blockade

Abstract: ◥Despite unprecedented advances in the treatment of cancer through the use of immune checkpoint blockade (ICB), responses are not universal and alternative strategies are needed to enhance responses to ICB. We have shown previously that a novel polyamine blocking therapy (PBT), consisting of cotreatment with a-difluoromethylornithine (DFMO) to block polyamine biosynthesis and a Trimer polyamine transport inhibitor, decreases myeloid-derived suppressor cells (MDSC) and M2-like tumor-associated macrophages (TAM)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…These results are consistent with the results of our recent study where polyamine blockade promoted CD8 + T-cell infiltration and worked in concert with anti-PD1 or anti-PDL1 immunotherapy to further promote animal survival in mouse models of glioblastoma [ 73 ]. The combinatorial effect of polyamine blockade and checkpoint immunotherapy was also demonstrated in mouse models of mammary carcinogenesis [ 76 ]. The results of these studies clearly demonstrate that polyamine blockade can alter the TME to promote immune functionality.…”
Section: The Role Of Polyamines In Cancer Immunosuppressionmentioning
confidence: 99%
“…These results are consistent with the results of our recent study where polyamine blockade promoted CD8 + T-cell infiltration and worked in concert with anti-PD1 or anti-PDL1 immunotherapy to further promote animal survival in mouse models of glioblastoma [ 73 ]. The combinatorial effect of polyamine blockade and checkpoint immunotherapy was also demonstrated in mouse models of mammary carcinogenesis [ 76 ]. The results of these studies clearly demonstrate that polyamine blockade can alter the TME to promote immune functionality.…”
Section: The Role Of Polyamines In Cancer Immunosuppressionmentioning
confidence: 99%
“…PBT-associated anti-tumor immune response has been tested in colon carcinoma and melanoma preclinical studies [ 15 , 20 ]. Studies have also shown the success of combining PBT with anti-PD-L1 therapy in mammary carcinoma and melanoma xenograft models [ 22 ]. Furthermore, preclinical studies from our group using PBT showed increased survival of pancreatic tumor-bearing mice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamine blocking therapy (PBT) can redirect the differentiation of MDSCs to pro-inflammatory M1-like macrophages through the downregulated expression of p-STAT3, an oncogenic transcription factor whose activation is implicated in MDSCs differentiation and survival. PBT significantly enhanced the antitumor efficacy of PD-1 blockade in both 4T1 mammary carcinoma and B16F10 melanoma tumors resistant to anti-PD-1 monotherapy, increasing tumor-specific cytotoxic T cells and survival of tumor-bearing animals beyond that with PBT or PD-1 blockade alone ( 99 ). Several studies indicate that all-trans retinoic acid (ATRA) is another agent that can promote myeloid cells maturation and reduce the number of MDSCs in the TME.…”
Section: Therapeutic Targeting Of Mdscs To Improve the Efficiency Of Icbmentioning
confidence: 99%